Valuation and returns of drug development companies: lessons for bioentrepreneurs and investors - Michaeli, Daniel; Yagmur, Hasan Basri; Achmadeev, Timur; Michaeli, Christoph T. (Therapeutic innovation & regulatory science, 2022)
This study evaluates the association of Biopharma company valuation with the lead drug’s development stage, orphan status, number of indications, and disease area. We also estimated annual returns Bioentrepreneurs and investors can expect from founding and investing in drug development ventures.